2010
DOI: 10.1292/jvms.09-0285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Fentanyl Administration on End-Tidal Sevoflurane Concentrations in Thoroughbred Racehorses undergoing Orthopedic Surgery

Abstract: ABSTRACT. To evaluate the effects of IV fentanyl administration on the end-tidal sevoflurane concentration (ET SEVO ) in thoroughbred racehorses, the ET SEVO required for internal fixation of longitudinal fractures was compared between horses anesthetized with sevofluranefentanyl (Group SF; n=9) and those anesthetized with sevoflurane alone (Group S; n=9). The loading dose of fentanyl (5.0 g/kg) was administered over 15 min followed by a maintenance dose of fentanyl (0.1 g/kg/min) throughout the operation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
0
17
2
1
Order By: Relevance
“…; Ohta et al. ). Dexmedetomidine, however, has been reported to have a significant impact on hemodynamic variables when administered as an infusion to isoflurane‐anesthetized ponies (Marcilla et al.…”
Section: Introductionmentioning
confidence: 97%
“…; Ohta et al. ). Dexmedetomidine, however, has been reported to have a significant impact on hemodynamic variables when administered as an infusion to isoflurane‐anesthetized ponies (Marcilla et al.…”
Section: Introductionmentioning
confidence: 97%
“…Fentanyl and remifentanil have been used in horses for analgesia and PIVA as part of a balanced anesthesia technique, but their long‐term use has not been reported (Ohta et al. ; Benmansour et al. ).…”
Section: Introductionmentioning
confidence: 99%
“… . We previously reported that the mean ET SEVO concentrations required for arthroscopic surgery and internal fixation were 2.8 ± 0.1% [ 20 ] and 3.0 ± 0.3% [ 19 ], respectively, when anesthesia was maintained with sevoflurane alone. We have also reported that medetomidine CRI reduced the mean ET SEVO concentrations required for arthroscopic surgery by approximately 10% [ 20 ].…”
mentioning
confidence: 99%
“…MAP was maintained above 70 mmHg throughout anesthesia. We previously reported that the mean dobutamine infusion rate required for keeping MAP between 60 and 80 mmHg was 0.90 ± 0.16 µ g/kg/hr when anesthesia was maintained with sevoflurane alone for internal fixation [ 19 ]. The dobutamine infusion rate required for keeping MAP within the target value was much lower in the current case ( Fig.…”
mentioning
confidence: 99%